Peningkatan Pembelajaran Inquiri Berbantuan Mind Mapping untuk Meningkatkan Prestasi Belajar pada Pokok Bahasan Sistem Persamaan Linear Dua Variabel Di Kelas VIII MTs Miftahul Ulum Bawean - Zubaidah Zubaidah; Sholahudin Al'ayubi (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2018)
Learning activity in education, especially in formal education that takes place in school, is an active interaction between teachers and students. Based on research in class VIII MTs Miftahul Ulum, student learning activity is still relatively low, students always be neutral toward student achievement that is achieved and also less than maximum. Mastery of learning and absorption in class VIII, respectively were: 58,83, 56,83% and 58,83%. This study used inquiri instruction model with the help of mind mapping on the subject of SPLDV Purpose to improve learning achievement. This research used classroom action research (PTK) with cycle models. Based on the results of the study, the classical mastery reached 77.50% ≥ 75%. While in cycle II, there were 20 students that had been completed individually and 6 students who had not achieved complete individually. Moreover, generally the total mean of the class reached 87.50≥75%. Implementation of research on cycle II was also completed. Keywords : Inquiry learning assisted mind mapping, learning achievement